Classic Jazz : A Personal View of the Music and the Musicians - Levin, Floyd (Book collections on Project MUSE., 2000)
Floyd Levin, an award-winning jazz writer, has personally known many of the jazz greats who contributed to the music's colorful history. In this collection of his articles, published mostly in jazz magazines over a fifty-year period, Levin takes us into the nightclubs, the recording studios, the record companies, and, most compellingly, into the lives of the musicians who made the great moments of the traditional jazz and swing eras. Brilliantly weaving anecdotal material, primary research, and music analysis into every chapter, Classic Jazz: A Personal View of the Music and the Musicians is a.